Recent advances in radiosensitivity determinants in melanoma. Issue 2 (10th March 2022) - Krayem, Mohammad; Ghanem, Ghanem E.; Van Gestel, Dirk
Abstract : Purpose of review: Radiotherapy has been proven to be useful but insufficient in melanoma management due to the intrinsic radioresistance of melanoma cells. Elucidation of the molecular mechanisms and pathways related to resistance/sensitivity to radiotherapy in melanoma is of paramount importance. In this review, we will summarize and discuss the recent 'discoveries' and advances in radiosensitivity determinants in melanoma. Recent findings: The different levels of radiosensitivity among the various melanoma tumors could be attributed to the DNA damage signaling and repair proteins, tumor microenvironment, hypoxia, cell metabolism, glutathione and redox balance, protein kinase signaling pathways as well as pigmentation and melanin content. Summary: It is therapeutically important to elucidate the factors involved in radiation resistance/sensitivity of melanoma. More importantly, improving radiosensitivity may 'widen the clinical utility' in melanoma of this important therapeutic modality.